Effect of Social Media Networking Sites on University Students - Kayode Muhammed Ibrahim; Emmanuel Ayeni; Oluwagapupo Peter Akinjide (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Social media sites play a significant role in the present generation especially among university students. The research assess the effect of networking site on Students’ Academic Performance and examine the effect of social networking site on Students’ extra curriculum activities. Data were analyzed using descriptive statistics and multiple regression analysis. The study found that there is positive relationship between social networking site and students’ academic performance, the analysis also revealed that there is significant relationship between social networking site and students’ extra curriculum activities. The study therefore recommends that Social media sites are a strong tool that can support excellent academic performance to university students. Students should therefore be allowed to have a choice of social media site they are willing to use especially when using it for learning.